Human breast milk: is it the best milk to prevent HIV transmission? - Paolo Palma (Elsevier, 2016)
A significant proportion of mother-to-child transmission (MTCT) of HIV still occurs during breastfeeding in settings where replacement feeding is unsafe and impractical. However, very few babies born to HIV-infected women and breastfed during the first 6 months of life become infected postnatally. The fact that the majority of babies who are breastfed by HIV-infected mothers remain uninfected even after several months of breastfeeding constitutes one of the major enigmas of HIV transmission via breast milk.